Nrf2 Deficiency Exacerbates Parkinson’s Disease by Aggravating NLRP3 Inflammasome Activation in MPTP-Induced Mouse Models and LPS-Induced BV2 Cells - Lu R; Zhou X; Zhang L; Hao M; Yang X (Dove Medical Press, 2024)
Ranran Lu,1,2,* Xu Zhou,1,2,* Lijie Zhang,3 Mengdie Hao,1,2 Xinling Yang1,4 1Department of Neurology, The Second Affiliated Hospital of Xinjiang Medical University, Ürümqi, Xinjiang, People's Republic of China; 2Xinjiang Key Laboratory of Neurological Disease Research, Ürümqi, Xinjiang, People's Republic of China; 3Xinjiang Production and Construction Corps Hospital, Ürümqi, Xinjiang, People's Republic of China; 4Xingjiang Medical University, Ürümqi, Xinjiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Xinling Yang, Department of Neurology, The Second Affiliated Hospital of Xinjiang Medical University, No. 38, Nanhu East Road, Shuimogou District, Urumqi, Xinjiang, 830026, People's Republic of China, Tel +86-13139699251, Email yangxinling2014@163.comBackground: Parkinson's disease (PD) is a movement disorder characterized by the progressive loss of dopamine neurons. Microglia-mediated neuroinflammation drives disease progression and becomes a critical factor in neuronal degeneration. Recent studies have found that nuclear factor-erythroid 2-related-2 (Nrf2) expression levels are reduced during aging and neurodegenerative diseases, but its regulatory mechanism on microglia-induced neuroinflammation has not been fully elucidated.Methods: In vivo, we used the intraperitoneal injection of the neurotoxic drug neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) to establish an animal model of PD and, at the same time, administered Nrf2 inhibitors ML385 and dimethyl fumarate to regulate Nrf2 protein levels. In vitro, we used si-RNA to knock out the Nrf2 gene to intervene in BV2 cells and used lipopolysaccharide (LPS) to stimulate and induce the cell model.Results: The study found that inhibition of Nrf2 expression aggravated the motor defects of PD mice, accompanied by a significant loss of dopaminergic neurons in the substantia nigra and striatum of the brain. In addition, after inhibition of Nrf2, the malondialdehyde (MDA) level in the substantia nigra of the midbrain of mice increased, and the levels of superoxide dismutase (SOD) and heme oxygenase-1 (HO-1) decreased, accompanied by the proliferation of microglia and astrocytes. In addition, the activation of the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome, the assembly of apoptosis-associated speck-like protein containing a CARD (ASC) protein in microglia, and the release of downstream inflammatory factors caspase-1 and interleukin (IL)-1β, were aggravated. At the cellular level, it was found that knocking out the expression of Nrf2 would aggravate the activation of NLRP3 inflammasomes and the assembly of ASC in LPS-induced BV2 cells.Conclusion: Inhibited Nrf2 activity can reduce the downstream antioxidant enzyme HO-1 and antioxidant levels, induce NLRP3 inflammasome activation and ASC protein assembly in microglia, and ultimately aggravate PD inflammatory response and dopamine neuron degeneration.Keywords: Parkinson's disease, Nrf2, oxidative stress, NLRP3 inflammasome, microglia